Peran Kepemimpinan Kepala Sekolah dalam Meningkatkan Kedisiplinan Guru - Badhar Satria Pratama; Yuli Aisyah; Imam Fahrur Rozy (PT. Hasba Edukasi Mandiri, 2025)
This literature-based article analyzes how principal leadership improves teachers’ discipline. Synthesizing empirical and review studies (2020–2025), we map (i) the disciplinary dimensions targeted in schools (attendance, punctuality, instructional preparation, administrative compliance, and classroom conduct), (ii) leadership mechanisms (vision-setting, role modeling, academic supervision, performance management, and school culture), and (iii) enabling conditions (teacher motivation, management practices, and digital monitoring). Evidence consistently indicates principal leadership exerts a positive, significant effect on teacher discipline and downstream performance. We conclude with a practical framework of leadership actions and monitoring indicators for schools.